توجيه قراءة الإمام نافع عند ابن عطية في تفسير من خلال سورتي المائدة والأنعام - عطية, كنزة (جامعة الوادي university of eloued, 2023)
يتناول هذا البحث الحديث عن توجيه قراءة الإمام نافع عند ابن عطية في تفسيره من خلال سورتي المائدة والأنعام وذلك في ثلاث مباحث: الأول ذكرت فيه التعريف بمصطلحات العنوان. المبحث الثاني ذكرتُ فيه منهجه في عرض القراءات وتوجيهها، عزو ابن عطية للقراءات بنسبتها إلى أصحابها والثالث مصادره في توجيه القراءات. وأما المبحث الثالث ذكرت فيه بعض النماذج التطبيقية من سورتي المائدة والأنعام حسب ما وجهها الإمام ابن عطية، والتي بينتها حسب موارد توجيه القراءات. وخلُصتُ في هذا البحث إلى جملة من النتائج أهمها: تنوع منهج ابن عطية في عرض وعزو وتوجيه القراءات. This research deals with the hadeeth about directing the reading of Imam Nafeh at Ibn Attia in his interpretation through Surahs Al-Maeda and Al-An'am, in three topics: the first in which I mentioned the definition of the terminology of the title. The second topic mentioned his approach in presenting and directing the readings, attributing Ibn Atiyah to the readings by attributing them to their owners, and the third is his sources in directing the readings. As for the third topic, I mentioned some applied examples from Surat Al-Ma’idah and Al-An’am, as directed by Imam Ibn Attia, which I showed according to the resources for directing the readings. In this research, I concluded a number of results, the most important of which.
تفسير
Keywords: توجيه القراءات، الإمام ابن عطية، الإمام نافع، المحرر الوجيز.; the diversity of Ibn Atiyah's approach in presenting, attributing, and directing the readings.